Teaching and Learning Writing on Descriptive Text - Ade Mulyadi (Universitas Islam Al-Ihya Kuningan, 2021)
The research was aimed to know process teaching and learning writing on descriptive and the reason why the teaching and learning process of English writing on descriptive conducted as it was observed. The research was in the form of a case study. The object of the research was the teaching and learning English writing at class X-3 of Senior High 1 Luragung in Academic Year 2015/2016. The main data analyzed using five steps: (a) analyzing; (b) interpreting; (c) summarizing; (d) concluding and implementing; and (e) recommending. Based on the findings, researcher concluded that the teaching learning process of English writing ran well, active and in general can achieve the learning objectives determined in the Lesson Plan. The material which has taught by the teacher includes the material of descriptive text. The result of evaluation is good. Most of students can reach minimum Passing Score 75. Only 12 students or 36,3 % from 33 students who get score under the minimum passing score in multiple choice test and writing composition, only 11 students or 33.3% from 33 students who get score under the minimum passing score in writing composition.